Strategy of Recruitment and Selection for Indonesian National Police (POLRI) Candidates - Dedy Yudanto; Pantius Drahen Soeling (Khazanah Sosial, 2023)
The industrial revolution 4.0 in Indonesia requires the National Police to revamp the recruitment system where the ideal personnel ratio has not been met, and Recruitment has not been prioritized on local wisdom. To fulfill Polri's HR in quantity and quality (predictive, responsive, and fair transparency) will be largely determined by the right personnel recruitment system because, without quality human resources, the Polri organization will find it difficult to achieve its vision and mission. The theories used are HR management theory, recruitment theory, and capability theory. There is a shortage of personnel provision in the Polri organization because the personnel intake has not been optimal with the number of personnel shrinking that has occurred. If viewed from the quality aspect, there is still a lack of knowledge, ability, and attitude of prospective Polri personnel in participating in the selection of Polri personnel supply due to the large interest of the community, which is not accompanied by strengthening the capacity of prospective Polri personnel. To strengthen the Recruitment of the National Police, it is also necessary to improve, organize, and change every process of providing Polri human resources at every stage of Recruitment and selection.